Mediation Role of C-Reactive Protein on the Association between Smoking Quantity and Type 2 Diabetes in Current Chinese Smokers - Dan Feng; Tao Liu; Hui Wang; Emma Karp; Wenhua Ling; Wei-Qing Chen (Journal of Diabetes Research)
Objective. Previous studies have indicated that cigarette smokers are more likely to develop type 2 diabetes and that both smoking and type 2 diabetes are associated with C-reactive protein (CRP). This study examined whether CRP mediates the association between smoking quantity and type 2 diabetes. Methods. Nine hundred and eighty-four current Chinese smokers were selected from a community-based chronic disease survey conducted in Guangzhou and Zhuhai. Type 2 diabetes was defined according to the WHO 1999 criteria. CRP was measured with flow cytometry. Binary logistic regression was performed to assess the mediation. Results. A positive association was observed between smoking quantity and type 2 diabetes (P<0.05). After controlling for potential confounders, daily cigarette consumption was significantly associated with higher CRP levels. Current smokers with type 2 diabetes had higher CRP levels than smokers without type 2 diabetes. The association between the smoking quantity and type 2 diabetes was mediated by CRP, which accounted for 50.77% of the association. Conclusions. This study provides further evidence that smoking quantity is positively associated with type 2 diabetes and suggests that the association between smoking and type 2 diabetes might be mediated by CRP.